KOMPENSASI EKSEKUTIF DAN KINERJA OPERASIONAL PERBANKAN INDONESIA - Santi Puspita Sari; Puji Harto (Diponegoro Journal of Accounting, 2014)
This study aimed to analyze the influence of executive compensation on the operational performance of banking in Indonesia. The data which are used in this study were obtained from the Indonesian Banking Directory in the year of 2009-2011. Samples were selected by purposive sampling method and finally obtained 32 banking companies per year that fulfill the criterias.The data were analyzed using multiple linear regression analysis model. The results showed that compensation of the excecutive give the significant possitive effects on the bank performance.